The study of the antimicrobial properties of selected plants growing in the Free State - Magama, Sibusisiwe (University of the Free State, 2000)
The Free State province has a rich diversity of indigenous woody plant species that exhibit antimicrobial activity towards both plant and human pathogens. Most of the province (about 72%) is located within the Grassland Biome, only about 21% is in the Nama-Karoo Biome, 6.64% in the Savanna Biome and with the Forest Biome making up only 0.05% of the province. The location of the province in what is mostly the Grassland Biome has resulted in extensive animal husbandry and intensive crop production. Grazing by animals, especially cattle and sheep, continues to have detrimental effect on the local pristine vegetation. On the other hand, intensive crop production, though done with utmost care in most cases, is also resulting in environmental degradation through water pollution by herbicides, both antimicrobials and insecticides. Chances are that some of these pesticides might end up in the food consumers buy, and may lead to health problems. There is great awareness in the Free State province for the need to conserve the environment and the fact that conservation can only be done through the knowledge of the vegetation ecology of the province. Towards this end, a lot of studies on the vegetation ecology of the different areas of the province have been attempted by a number of authors. Despite the existence of information on the vegetation ecology, the Free State still had to be mapped for plants with biological activities, in our case, antimicrobial activity. This exercise was successfully done. Antimicrobial screening of the crude extracts was done as a preliminary screen to determine which plant species exhibited this activity. Bench top assays were used due to their reliability, speed and cost effectiveness. The screen gave valuable information on the antimicrobial properties of these selected plants. By referring to their phytochemical compositions m literature, we were able to conclude why they are used in ethnopharmacology, as well as determine the active principles. Antibiotic plant species with ethnopharmacological value can also be used as agrochemieals against plant pathogenic miroorganisms with success. The extracts of selected plant species in our investigations were tested against both plant and human pathogens with encouraging results. The general absence of antifungal activity towards plant pathogenic fungi was attributed to lower doses of the extracts used, the crude nature of the extracts as well as the the probable presence of growth promoters for the fungi or the general absence of active antifungal substances by nature. The crude extracts of seven plant species out of a total of twenty six exhibited the most outstanding antibacterial activity as evidenced by broad spectrums of activity and larger inhibition zones in comparison with the rest of the plant species. The most resistant bacterial pathogen towards the crude extracts was Erwinia carotovora pv. carotovora while the least resistant was Moraxella catarrhalis. From the seven most active plant species, it was decided to do further investigations on Euclea crispa subsp. crispa. This was due to the fact that it is widely used in ethnopharmacology in areas like Kwa-Zulu Natal and also that it is one of the most common plant species in the province as well as in the country as a whole. The crude and semi-purified (liquid-liquid separation) extracts of E. crispa subsp. crispa showed antibacterial activity towards human pathogenic bacteria to varying degrees. The ethyl acetate fraction was the most active however, since only three human pathogenic bacteria were not inhibited by it. Klebsiella pneumoniae was the most resistant human pathogenic bacterium. With regards to plant pathogenic bacteria, generally, only the ethyl acetate fraction and (the crude extract) showed activity against all the bacteria. Antifungal screening of the semipurified extracts with human pathogenic fungi also showed that most of the antifungal activity was located in the ethyl acetate fraction. No antifungal activity was observed with the hexane fraction. Due to the more complex nature of the crude extract, further phytochemical studies were carried out only with the ethyl acetate fraction, the most active semi-purified fraction. Investigations into the general phytochemical profile of the ethyl acetate fraction of E. crispa subsp. crispa revealed that the plant extract contained essential oils, bitter principles, saponins, alkaloids and phenolic compounds; the first three being terpenoid derivatives. Bitter principles are in some cases reported as being mixtures of different classes. A terpenoid that tested positive for bitter principles and for saponins as well as possessing a steroid-like structure was isolated from the ethyl acetate fraction. This compound was active against M catarrhalis. Also isolated from the ethyl acetate fraction and showing antimicrobial activity were five flavonoids identified as hyperoside, quercitrin, catechin, epicatechin and gallocatechin. The most active flavonoids were epicatechin and hyperoside which inhibited the growth of Streptococcus pneumoniae and Haemophilus injluenzae respectively. The activities of the isolated flavonoids towards human pathogenic bacteria were lower than that that of the more complex ethyl acetate fraction. The conclusion arrived at was that these compounds function in synergy in the latter more complex fraction. Since most of the plant extracts are used in the form of complex mixtures in ethnopharmacology, a suggestion was made to use the ethyl acetate fraction in its complex form. It was further acknowledged that the use of complex mixtures instead of pure compounds does not eliminate the need to determine the chemical composition of the complex mixtures. This is necessary to determine the dosages and toxicity of the constituents of the extracts. In conclusion, it can be said that valuable information on the antimicrobial properties of selected plant species growing in the Free State Province was obtained during the course of our investigations. Also of value is the information on the distribution of these species in relation to biomes, geology and soil types. The availability of literature on the vegetation ecology of different parts of the province was also of immense help to us during this investigation.

Die Oranje Vrystaat beskik oor 'n ryk diversiteit van inheemse houtagtige plant spesies wat antimikrobiese aktiwiteit openbaar teenoor bëide plant- en mens patogene. Die grootste gedeelte van die provinsie (ongeveer 72%) is geleë binne die Grasland Bioom, slegs 21% is in die Nama-Karoo Bioom, 6.64% in die Savanna Bioom terwyl die Bos Bioom slegs 0.05% van die provinsie uitmaak. Die lokaliteit van die provinsie, hoofsaaklik Grasland Bioom, het aanleiding gegee tot ekstensiewe vee - en intensiewe gewasproduksie. Weiding deur diere, veral skape en beeste, het 'n vernietigende effek op die pristien vegitasie. Aan die ander kant gee intensiewe gewasproduksie, alhoewel met sorg beoefen, ook aanleiding tot die agteruitgang van die omgewing as gevolg van die gebruik van onkruiddoders, antimikrobiese middels en insekdoders. Die kans bestaan dat van hierdie chemikalieë in voedsel wat deur verbruikers gekoop word mag opeindig en potensieël tot gesondheidsprobleme mag aanleiding gee. Daar is egter 'n bewustheid vir die behoefte om die omgewing van die Oranje Vrystaat provinsie te bewaar en die feit dat bewaring alleen moontlik is as ons oor die nodige vegitasie ekologie kennis van die provinsie beskik. Om hierdie doel te verwesenlik, is baie vegitasie ekologie studies reeds onderneem deur verskeie outeurs. Ten spyte van die bestaan van hierdie inligting, moes die provinsie nog vir plante wat biologiese aktiwiteit toon, in ons geval antimikrobiese aktiwiteit, gekarteer word. Hierdie oefening is met 'n redelike mate van sukses uitgevoer. Die toetsing van ru-ekstrakte vir anti-mikrobiese aktiwiteit was as 'n voorlopige studie uitgevoer ten einde vas te stel watter plante in hierdie kategorie val. Laboratorium essaheringstegnieke is gebruik vanweë hulle betroubaarheid, koste-effektiwiteit en spoed waarteen vinnige resultate bekom kan word. Hierdie voorlopige toetsing het waardevolle inligting met betrekking tot die antimikrobiese potensiaal van plante opgelewer. Deur ook na die plante se fitochemiese samestellings, soos in die literatuur vervat te verwys, was ons instaat om vas te stel waarom baie van hierdie plante etnobotaniese gebruike het asook om die aktiewe bestanddele hiervoor verantwoordelik te identifiseer. Plant spesies met antibiotiese en dus etnofarmakologiese potensiaal kan ook as agrochemikalieë met sukses teen plantpatogeniese mikroorganismes ingespan word. In hierdie studie is ekstrakte van selektiewe plantspesies teen beide plant- en menspatogene getoets en met belowende resultate. Die algemene afwesigheid van anti-fungale aktiwiteit by hierdie plante kan moontlik toegeskryf word aan die lae dosisse van toets ekstrakte deur ons gebruik, die moontlike aanwesigheid van fungale groei stimuleerders of selfs die natuur-like afwesigheid van antifungale aktiewe bestandeie by hierdie plante. Sewe plantspecies uit 'n totaal van 26 het bo-gemiddelde antibakteriese potensiaal getoon soos aangedui deur die breë spektrum van beheer asook groter inhibisie sones in vergelyking met die res. Die mees weerstandbiedende bakteriese patogeen was Erwinia carotovora pv. carotovora terwyl die mees sensitiewe een Moraxella catarrhalis was. Daar is egter besluit om verdere studies slegs op Euclea crispa subsp. crispa uit te voer angesien dit die meeste etnofarmakologiese toepassing geniet maar ook omdat dit so wyd versprei in die provinsie en die land aangetref word. Die ru- en semi-gesuiwerde ekstrakte van E. crispa subsp. crispa het antibakteriese aktiwiteit met variërende intensiteit teen mensbakterieë getoon. Geen besondere patroon is waargeneem nie maar die etielasetaat fraksie was die mees aktiewe een. Met betrekking tot plantpatogeniese bakterieë het slegs die ru- ekstrak en etielasetaat fraksie enige aktiwiteit getoon. Antifungale toetsing op menslike swamme het ook aktiwiteit in slegs die ru-ekstrak en etielasetaat fraksie uitgewys. Geen aktiwiteit is met die nie-polêre heksaan fraksie waargeneem nie. Vanweë die meer komplekse aard van die ru-ekstrak, is verdere fitochemiese studies slegs met die etielasetaat fraksie uitgevoer wat naas die ru-ekstrak, as die mees aktiewe semi-gesuiwerde fraksie uitgestaan het. 'n Ondersoek na die algemene fitochemiese profiel van die etielasetaat fraksie van E. crispa subsp. crispa, het daarop gedui dat die plant ryk is aan essensiële olies, bitter bestanddele, saponiene en fenoliese verbindings. Die eerste drie is almal terpenoïed derivate. Vyb flavonoïede is geïsoleer en geïdentifisser naamlik hiperosied, quersitrien, catachien, epicatechien en gallocatechien. Die aktiwiteit van die geïsoleerde flavonoïede teen menspatogeniese bakterieë was laer as dié van die meer komplekse etielasetaat fraksie. Die gevolgtrekking hieruit is dat die verbindings waarskynlik sinergisties funksioneer in laasgenoemde meer komplekse fraksie. Aangesien meeste plantekstrakte etnofarmakologies in die vorm van komplekse mengsels gebruik word, is 'n aanbeveling dan ook gemaak dat die etielasetaat fraksie net so in sy komplekse vorm gebruik word. Dit is ook verder erken dat die gebruik van komplekse mengsels eerder as suiwer komponente nie die behoefte vir die bepaling van die afsonderlike komponente in die mengsel se chemiese strukture wegneem nie. Laasgenoemde is steeds belangrik ten einde die dosisse en toksisiteit van afsonderlike konstituente te bepaal. In die toekoms behoort hierdie flavonoïede meer intensief teen plantpatogeniese bakterieë en swamme getoets te word. Ten slotte kan die steling gemaak word dat waardevolle inligting met betrekking tot die antimikrobiese eienskappe van geselekteerde plante in die Oranje Vrystaat met hierdie studie bekom is. Ook van waarde is die inligting oor die verspreiding van hierdie spesies in verhouding tot die bioom, die geologie en die grond tipes van die provinsie. Die beskikbaarheid van literatuur oor die vegitasie ekologie van die verskillende streke van die provinsie was egter van groot hulp tydens hierdie studie.
Thesis (Ph.D. (Agronomy and Plant Pathology))--University of the Free State, 2000
Keywords: Plants -- Analysis; Anti-infective agents; Plant antiviral agents; Plants -- Disease and pest resistance -- South Africa -- Free State